Musclin Is Related to Insulin Resistance and Body Composition, but Not to Body Mass Index or Cardiorespiratory Capacity in Adults (2021)
Background: We studied whether musclin function in humans is related to glycemic control, body composition, and cardiorespiratory capacity. Methods: A cross-sectional study was performed in sedentary adults with or without metabolic syndrome (MS). Serum musclin was measured by enzyme-linked immunosorbent assay. Insulin resistance (IR) was evaluated by the homeostatic model assessment (HOMA-IR). Body composition was determined by dual-energy X-ray absorptiometry and muscle composition by measuring carnosine in the thigh, a surrogate of fiber types, through proton magnetic resonance spectroscopy. Cardiorespiratory capacity was assessed through direct ergospirometry. Results: The control (n=29) and MS (n=61) groups were comparable in age (51.5±6.5 years old vs. 50.7±6.1 years old), sex (72.4% vs. 70.5% women), total lean mass (58.5%±7.4% vs. 57.3%±6.8%), and peak oxygen consumption (VO2peak) (31.0±5.8 mL O2./kg.min vs. 29.2±6.3 mL O2/kg.min). Individuals with MS had higher body mass index (BMI) (30.6±4.0 kg/m2 vs. 27.4±3.6 kg/m2), HOMA-IR (3.5 [95% confidence interval, CI, 2.9 to 4.6] vs. 1.7 [95% CI, 1.1 to 2.0]), and musclin (206.7 pg/mL [95% CI, 122.7 to 387.8] vs. 111.1 pg/mL [95% CI, 63.2 to 218.5]) values than controls (P˂0.05). Musclin showed a significant relationship with HOMA-IR (β=0.23; 95% CI, 0.12 to 0.33; P˂0.01), but not with VO2peak, in multiple linear regression models adjusted for age, sex, fat mass, lean mass, and physical activity. Musclin was significantly associated with insulin, glycemia, visceral fat, and regional muscle mass, but not with BMI, VCO2peak, maximum heart rate, maximum time of work, or carnosine. Conclusion: In humans, musclin positively correlates with insulinemia, IR, and a body composition profile with high visceral adiposity and lean mass, but low body fat percentage. Musclin is not related to BMI or cardiorespiratory capacity.